Inside Cover: A Reversible and Selective Inhibitor of Monoacylglycerol Lipase Ameliorates Multiple Sclerosis (Angew. Chem. Int. Ed. 50/2014). Issue 50 (22nd October 2014) - Hernández‐Torres, Gloria; Cipriano, Mariateresa; Hedén, Erika; Björklund, Emmelie; Canales, Ángeles; Zian, Debora; Feliú, Ana; Mecha, Miriam; Guaza, Carmen; Fowler, Christopher J.; Ortega‐Gutiérrez, Silvia; López‐Rodríguez, María L.
<x xml:space="preserve">Abstract</x> The inhibition of monoacylglycerol lipase (MAGL) the enzyme responsible for the inactivation of the endocannabinoid 2‐arachidonoylglycerol, is a strategy for the treatment of multiple sclerosis. In their Communication on page 13765 ff., M. L. López‐Rodríguez and co‐workers describe a potent, reversible, and selective inhibitor of MAGL that slows the clinical progression of multiple sclerosis without inducing undesirable CB1‐mediated side effect.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>